2023
DOI: 10.1126/sciadv.ade7172
|View full text |Cite
|
Sign up to set email alerts
|

Early life adversity and adult social relationships have independent effects on survival in a wild primate

Abstract: Adverse conditions in early life can have negative consequences for adult health and survival in humans and other animals. What variables mediate the relationship between early adversity and adult survival? Adult social environments represent one candidate: Early life adversity is linked to social adversity in adulthood, and social adversity in adulthood predicts survival outcomes. However, no study has prospectively linked early life adversity, adult social behavior, and adult survival to measure the extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 122 publications
(225 reference statements)
0
9
0
Order By: Relevance
“…Early life adversity in female baboons ( Papio sp. ) is associated with reduced fecundity and poorer offspring survival (Lange et al, 2023; Lea et al, 2015; Patterson et al, 2021; Tung et al, 2016, 2023; Weibel et al, 2020; Zipple et al, 2019). Organisms are hypothesized to adjust their developmental trajectories in response to early life adversity in order to improve immediate survival (Lea et al, 2017; Lea & Rosenbaum, 2020; Patterson, Petersen et al, 2023), but such adjustments may lead to these detrimental outcomes in adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early life adversity in female baboons ( Papio sp. ) is associated with reduced fecundity and poorer offspring survival (Lange et al, 2023; Lea et al, 2015; Patterson et al, 2021; Tung et al, 2016, 2023; Weibel et al, 2020; Zipple et al, 2019). Organisms are hypothesized to adjust their developmental trajectories in response to early life adversity in order to improve immediate survival (Lea et al, 2017; Lea & Rosenbaum, 2020; Patterson, Petersen et al, 2023), but such adjustments may lead to these detrimental outcomes in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Females who live longer have a longer reproductive span, and are able to produce more offspring. Long-term studies have shown that early life adversity is associated with reduced survival in adult female baboons and hyenas ( Crocuta crocuta ) (Gicquel et al, 2022; Lange et al, 2023; Strauss et al, 2020; Tung et al, 2016). In populations characterized by high mortality rates prior to reproductive maturity, LRS based on the total number of offspring reaching reproductive maturity is the best proxy for fitness (e.g., Alif et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Because we are less likely to observe a given grooming interaction in a large group compared to a small group, we included a measure of observer effort in our models of age at first grooming (e.g. [24,54]).…”
Section: Methods (A) Study Population and Study Subjectsmentioning
confidence: 99%
“…The importance of mothers for the development of social behaviour and fitness is also well-established in many species [3][4][5]24,25]. For example, in elephants, chimpanzees, and yellow baboons, early maternal loss, even after weaning, is associated with altered social relationships in adulthood [3][4][5]24,26] and reduced lifespan [8,10,12,24]. However, many gaps remain in our understanding of behavioural development in natural populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation